Investigation Of Kinetic Regularities For Obtaining Methyl-1,3,4- Trimethylcyclohex-3-Encarboxylate By Reaction Of Diels-Alder - Kostiv, I.S.; Havryliv, R.I. (Methods and Objects of Chemical Analysis, 2019)
Kinetics of the reaction of the cycloaddition of 2,3-dimethylbuta-1,3-diene (DMB) and methylmethacrylate (MMA) by the Diels-Alder reaction was studied. Reaction rate constants k = 4.4∙10-6 l/(mol∙s) at T = 403 K; k = 10.0∙10-6 l/(mol∙s) at T = 413 K; k = 15.8∙10-6 l/(mol∙s) at T = 423 K; k = 19.4∙10-6 l/(mol∙s) at T = 433 K and the activation parameters of the reaction Eakt = 75.2 kJ/mol, ΔS = -146.8 J/(mol∙K), ΔH = 73.9 kJ/mol were determined. Influence of temperature, molar ratio of reagents on the yield of the target product was investigated. At temperature increase from 403 to 433 K, methyl-1,3,4-trimethylcyclohex-3-encarboxylate (MTMCHC) yield increases from 78 % to 92 %. With further increase in temperature, DMB boils and MMA remains in a liquid state, accordingly it is not expected that the target product yield will materially increase. An increase in the excess of DMB: МMA from 1:1 to 2.5:1 makes it possible to increase yield of MTMCHC from 65 % to 92 %. The production of methyl-1,3,4-trimethylcyclohex-3-encarboxylate at the optimal conditions was established: temperature of 423−433 K and molar ratio of reagents DMB:MMA = 1.5:1, the yield of MTMCHC reaches 89−92 % at productivity of 101−105 g/(l·h). Based on the obtained reaction rate constants and the activation parameters of the [4+2]-cyclic addition of 2,3-dimethylbuta-1,3-diene and methylmethacrylate, it was found that the reaction under study is subject to the kinetic law of the second order.